Normal electromagnetic flux surfaces with the existence of the visco-modified effect - Körpınar, Talat; Demirkol, Rıdvan Cem; Körpınar, Zeliha (Springer, 2022)
In this paper, the features of current magnetic and electric flow densities are investigated. Their geometric phases computed through the local anholonomic reference frame are investigated for the normal flow of the electromagnetic field lines in ordinary geometry. The normal evolution field-based reference frame, which specifies the time-dependent flow of the curve in terms of geometric quantities, is given. The relationship of the gradient of the flow flux and the divergence freeness of the magnetic field is introduced. Thus, the aim is to elucidate the efficient use of the anholonomic coordinate system and its components and also to determine the conditions for the existence of electromagnetic field vector flux surfaces governed by evolution equations in the normal direction when they are exposed to the modified visco Heisenberg ferromagnetic effect.
Keywords: Normal motion; Flow density; Flow phase; Modified visco Heisenberg effect; Ferromagnetism; Ferromagnetic Spin; Equation; Instabilities; Evolution; Family; Wave